Effect of nitrogen and iron supplementation on the process performance and microbial community structure of a hydrogen-producing reactor continuously fed with tequila vinasse. (15th February 2023) - García-Depraect, Octavio; Mena-Navarro, Vanessa; Muñoz, Raúl; Rene, Eldon R.; León-Becerril, Elizabeth
Highlights: Unbalanced C/N ratio may cause over-growth of lactic acid bacteria (LAB). Adequate C/N ratio may boost balance and syntrophy between LAB and H2 -producers. Resilience to process perturbations is key for high-rate hydrogen production. Biohythane production: 14.2 kJ g-VS −1, 81 NmL-H2 g-VS −1  + 543 NmL-CH4 g-VS −1 . Abstract: Dark fermentation is gaining importance as a bioprocess able to valorize different organic wastes/wastewaters through the co-production of organic acids and biogenic hydrogen (bioH2 ). In this study, the process performance and microbial community structure of a mesophilic lab-scale fermenter inoculated with an enriched hydrogenogenic consortium and fed with undiluted tequila vinasse (TV) were evaluated for 28 days equivalent to 112 hydraulic retention times (HRT). The influence of external nutrients supply on process performance was carefully evaluated. The fermenter was operated at 6 h HRT and fed with i) TV without additional nutrients, ii) TV with additional nitrogen (0.3 g/L), and iii) TV supplemented with nitrogen (0.3 g/L) and iron (0.01 g/L) chemical sources. Despite the inherent presence of macro- and micronutrients in TV, the use of raw TV with no additional nutrients resulted in a very low hydrogen production rate of 24 NmL-H2 L −1 h −1 . Contrarily, a nitrogen dosing of 1.2 g-NH4 Cl L −1 led to a sudden increase in the bioH2 production, reaching productivity and yield values of 283 NmL-H2 L −1 h −1 and 82 NmL-H2 g − 1 -volatile solids added, respectively. The further addition of FeSO4 ·7H2 O (0.05 g/L) did not improve the TV-to-bioH2 conversion. Bridging hydrogen production and organic acids with molecular analysis, 16S rRNA gene sequencing, indicated that maintaining a suitable C/N ratio in the fermenter could ensure balance and syntrophy between lactic acid bacteria (e.g., Sporolactobacillus, Lactobacillus ) and bioH2 producers ( Clostridium ). Further biochemical methane potential tests with the fermentation broth demonstrated that biohythane process (bioH2  + CH4 ) resulted in 5 % higher bioenergy recovery than that derived from the single-stage anaerobic digestion.